On Becoming a Rock Musician. - Bennett, H. Stith (Legacy editions (Columbia University. Press), 2017)
In the 1960s and 1970s, becoming a rock musician was fundamentally different than playing other kinds of music. It was a learned rather than a taught skill. In On Becoming a Rock Musician, sociologist H. Stith Bennett observes what makes someone a rock musician and what persuades others to take him seriously in this role. The book explores how bands form; the backstage and onstage reality of playing in a band; how bands promote themselves and interact with audiences and music professionals like DJs; and the role of performance.